Complementizer Phrase in Central Kurdish - Omer Ahmad Azeez; Sabah Rashid Qadir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Complementary phrase is a type of functional phrases that exist in Kurdish in several forms, such as question words and complex sentences. There are many assumptions and presentations, which has led to different opinions on this topic. This motivated the writing of this article. In English the complementary phrase in the form of the question word has a strong feature, because the question word in English moves overtly and goes to the position of the spec of the CP and the Aux verb is in the position of the head of CP, but in kurdish does not have a strong feature, because the question word in Kurdish does not move in overt syntax except in a few cases. The head of the complementary phrase is in the form of null constitutent, because there is no auxiliary verb in Kurdish. In the form of complex sentences, complementary phrase in Kurdish appear in the case where the subordinating conjunction, or other words that form complex sentences, or those forms of words that precede the sentences. finally in this study we tried to compar the (WH) word movement in kurdish and English To explain the characteristics of this phrase in KurdishTherefore, we have chosen English because the theories and hypotheses are presented in that language.